Characterisation of colloidal nanosilica modified asphalt binder - Mohamad Saifullah, Samsudin; Ahmad Kamil, Arshad; K. A., Masri; Siti Norsita, Rawi; Hasmawati, Mat Hassan; Nurakmal Hayati, Mustakim (IOP Publishing, 2021)
Nanosilica (NS) has been used in this study as an asphalt binder modifier to improve the binder properties. Penetration grade 60/70 (PEN 60/70) asphalt binder was modified with NS in colloidal form with an average size of 10 to 15 nanometer (nm). The nanosilica modified asphalt binders (NSMB) were tested for different tests such as physical properties, atomic force microscopy (AFM), dynamic shear rheometer (DSR), multiples stress creep and recovery (MSCR) and asphalt pavement analyser (APA). The result obtained from physical properties shows that the additions of NS significantly improve the properties of base asphalt binder in terms of penetration, softening point and viscosity. It was also found that NSMB is stable during the high temperature storage period. SEM images showed that NS particles dispersed well in base asphalt binder and AFM images showed that the addition of nanosilica in asphalt binder improved its surface stiffness. In addition, NSMB significantly increases the G*/sinδ value, failure temperature, and percentage creep recovery while, decreased the non-recoverable creep compliance, which indicated higher elasticity and beneficial in increasing the rutting resistance as compared to the base asphalt. On the other hand, from APA test, it was found that NSMB reduced the rutting depth of asphalt mixture. It can be concluded from the analysis that a maximum of 2% NS be added into the base asphalt for optimum binder modification.